Answer:
The first derivative of the given function
![(df(x))/(dx) = - ab e^(-b x)](https://img.qammunity.org/2021/formulas/mathematics/college/68wg5x17w3lxdwrq3xr40v06dbdbgjtpbw.png)
Explanation:
Step(i):-
Given f(x) = ae⁻ᵇˣ ...( i )
we will use differentiation formula
![(d(e^(ax)) )/(dx) = a e^(a x)](https://img.qammunity.org/2021/formulas/mathematics/college/f3ark9x9enekhsml7w28mfrqb2f7q23ugf.png)
Step(ii)
Differentiating equation (i) with respective to 'x', we get
![(df(x))/(dx) = a e^(-b x) (d)/(dx) (-b x )](https://img.qammunity.org/2021/formulas/mathematics/college/olc8ohbmqbp9cno7y9oz6tywnqca44xsd3.png)
= -ab e⁻ᵇˣ
![(df(x))/(dx) = - ab e^(-b x)](https://img.qammunity.org/2021/formulas/mathematics/college/68wg5x17w3lxdwrq3xr40v06dbdbgjtpbw.png)
Final answer:-
The first derivative of the given function
![(df(x))/(dx) = - ab e^(-b x)](https://img.qammunity.org/2021/formulas/mathematics/college/68wg5x17w3lxdwrq3xr40v06dbdbgjtpbw.png)